STUDI LITERATUR: PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Tika Wulandari; Aninda Cahyani; Yuanda Enivita; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Learning facilities are an important factor in achieving learning outcomes. The completeness of learning facilities will help students in learning and the lack of learning facilities can hinder their learning progress. This study uses a literature review study method. The purpose of this study was to see the effect of learning facilities on the learning outcomes of elementary school students. Adequate learning facilities can improve the learning outcomes obtained by good students. This is due to the adequacy of facilities and infrastructure owned in learning